Hubungan Antara Religiusitas Dengan Kepuasan Pernikahan Pada Dewasa Madya - Pratiwi, Paramita Putri; Drs. Soleh Amini Yahman, M.Si, Psi, Drs. Soleh Amini Yahman, M.Si, Psi (2017)
The aim of this research is to understand: 1) the correlation between religious and marriage satisfaction in Medium-age. 2) Effective contribution of religious toward marriage satisfaction in Medium-age. 3) Religious. 4) Marriage satisfaction in Medium-age. The hyphothesis of this research is there is positive correlation between religious and marriage satisfaction in Medium-age. The subject of this research consists of 120 people in Medium-age. The population in this research is the inhabitant in Karanganyar regency both male and female in Medium-age (40-60 years old) which has married and as a moslem. Scale which used in this research is: a) Religious Scale and b) Marriage satisfaction scale. The technique of analyzing data in this research used Product Moment corelation. The conclusion of the hyphothesis is there is positive correlation between religious and marriage satisfaction in Medium-age who lives in Karanganyar. When the religious level in Medium-age is high, the marriage satisfaction will be high. In contrary, when the religious level in Medium-age is low, the marriage satisfaction will be low too. This research showed coeffisient r = 0.665 with the sig. 0.000 (p<0.01). The level of religious is high categorized. Marriage satisfaction of the research subject is high categorized too. It can be shown from the RE is 179.69 and RH is 145. SE of religious is 44.22 %. There are another reasons which effect marriage satisfaction for 55.78 %. For instance are communication, doing activity in leisure time, religious orientation, conflict resolution, financial management, sex contact, family and friends, children and children's education about caring in making decision for them, individual problem, and the role of egalitarian.